2018
DOI: 10.17827/aktd.346010
|View full text |Cite
|
Sign up to set email alerts
|

Uyku Bozuklukları: Sınıflama ve Tedavi

Abstract: Sleep can be defined as a different state of consciousness and is necessary for the normal and healthy functioning of the human body. Sleep disturbances are known to cause loss in functionality and decrease in quality of life and can occur primarily or due to another physical illness or mental disorder. The aim of this article is to overview the sleep disorders in the light of recent classification systems and treatment algorithms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
23

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 29 publications
0
5
0
23
Order By: Relevance
“…Differences in the definition, measurement, and evaluation of sleep-wakefulness disorders are responsible for the disparities in epidemiological results [2,14]. Nonetheless, nearly all the epidemiological studies report that insomnia, daytime sleepiness, and hypersomnia vary according to gender, age, and profession [9,14,15]. It has been reported that daytime sleepiness and idiopathic hypersomnia are common sleep complaints in females [14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Differences in the definition, measurement, and evaluation of sleep-wakefulness disorders are responsible for the disparities in epidemiological results [2,14]. Nonetheless, nearly all the epidemiological studies report that insomnia, daytime sleepiness, and hypersomnia vary according to gender, age, and profession [9,14,15]. It has been reported that daytime sleepiness and idiopathic hypersomnia are common sleep complaints in females [14].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, nearly all the epidemiological studies report that insomnia, daytime sleepiness, and hypersomnia vary according to gender, age, and profession [9,14,15]. It has been reported that daytime sleepiness and idiopathic hypersomnia are common sleep complaints in females [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Uyku kalitesi ve yorgunluğun incelendiği çalışmada uyku ve yorgunluk arasında pozitif yönde ilişkinin olduğu bulunmuştur. Bunun yanı sıra uyku bozukluklarının belirtileri arasında yorgunluğun olduğu da bilinmektedir (Keskin ve Tamam, 2018). Bu bilgiler dikkate alındığında yapılan bu araştırmanın bulgularının literatür ile paralellik gösterdiği ifade edilebilir.…”
Section: Tartışma Ve Sonuçunclassified